Comprehensive Review of Phytosomes: Formulation, Characterization, and Therapeutic Applications - Vaidya, Sunita N. (Asian Journal of Pharmaceutics (AJP), 2024)
The capacity of phytosomes to enhance the absorption and bioavailability of bioactive components from plant extracts has made them a notable breakthrough in the fields of dietary supplements and herbal medicine. Using this innovative method, plant extracts are molecularly complexed with phospholipids to produce lipid complexes that resemble cell membrane structures. Because of their structural similarity, these bioactive chemicals are better soluble and absorbed, which makes them easier for the body to use. Pharmaceuticals, nutraceuticals, cosmetics, and functional foods are just a few of the businesses that use phytosomes. Numerous health advantages have resulted from their adaptable use, including protection against antioxidants, improved cognitive function, liver health support, and cardiovascular well-being. However, individual reactions could differ, so exercise caution and seek advice from medical professionals, particularly when used in conjunction with prescription drugs or for particular medical conditions. Phytosomes offer a more effective and efficient way to extract the medicinal qualities of plant extracts, which is a promising development in herbal medicine and nutrition. Their capacity to augment the transportation of bioactive substances presents novel prospects for enhanced health and overall wellbeing, rendering them a remarkable augmentation to the domain of alternative medicines and dietary supplements.